Pendidikan untuk Anak Usia 0-2 Tahun dalam Perspektif Ibnu Qoyyim Al-Jauziyyah - Saputra, Angga; Maemonah, Maemonah (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
The purpose of this research is to find out the concept of Ibn Qayyim's thought in education for children age 0-2 years. This research uses descriptive content method with the type of library research. Documentation is used as data collection technique, and researcher as instrument. After the data waa obtained, the researcher processes the data by reading and analyzing and then concluding. The results of research conducted, are: (1) Education provided to children age 0-2 years includes: sounding adhan in the right ear of children, and iqomah in the left ear, taking the takhnik, aqiqah, hair shaving, giving a good name, breastfeeding until the age two years, and circumcision. (2) Implications of education according to Ibn Qoyyim on the development of children's potential are, the moral-religious, physical-motor, also cognitive and social-emotional potential.